The Development of Character-Based Intensive Reading Text Book in Elementary School - Wisda Miftakhul Ulum (Pascasarjana UM, 2014)
Pengembangan Buku Teks Membaca Intensif Berbasis Karakter di Sekolah DasarAbstract: The purpose of this study was (1) to develop instructional materials intensive reading of literary and non-literary class VI character-based, including materials and presentation techniques book. The products of this research is the development of intensive reading literary books and non-literary. Development of reading books of literary and non-literary intensive use development model of the development of teaching materials and the adaptation of Pannen Purwanto by step development of teaching materials from Tomlinson. Stages of development model is a preliminary analysis, the analysis of the curriculum, reading text collection, the selection of reading texts, writing and materials development, product testing, revision, and then the final product. Test subjects in the study were expert subjects and the learning of Indonesian language, character education experts, instructional media specialists, teachers and sixth grade students of SDN Pakis. The results of field tests of validity and intensive reading literary books and non-literary shows the criteria are very valid and ready to be used for the actual learning activities.Key Words: textbooks development, sixth grade intensive reading, character Abstrak: Tujuan penelitian ini adalah mengembangkan bahan ajar membaca intensif sastra dan non sastra kelas VI berbasis karakter, meliputi materi dan teknik penyajian buku. Produk penelitian pengem-bangan ini adalah buku membaca intensif sastra dan non sastra. Pengembangan buku membaca intensif sastra dan non sastra menggunakan model pengembangan bahan ajar hasil adaptasi dari Pannen dan Purwanto dengan langkah pengembangan bahan ajar dari Tomlinson. Tahapan model pengembangan adalah analisis pendahuluan, analisis kurikulum, pengumpulan teks bacaan, pemilihan teks bacaan, penulisan dan penyusunan bahan ajar, uji coba produk, revisi, kemudian produk akhir. Subjek uji dalam penelitian adalah ahli mata pelajaran dan pembelajaran bahasa Indonesia, ahli pendidikan karakter, ahli media pembelajaran, guru dan siswa kelas VI SDN Pakis. Hasil uji validitas dan uji lapangan buku membaca intensif sastra dan non sastra menunjukkan kriteria sangat valid dan dapat dimanfaatkan untuk kegiatan pembelajaran sebenarnya.Kata kunci: pengembangan buku teks, membaca intensif untuk kelas enam, karakter